Predicting factors of muscle necrosis in acute compartment syndrome of the lower extremity. Issue 2 (February 2020) - Mortensen, Sharri J; Zhang, Dafang; Mohamadi, Amin; Collins, Jamie; Weaver, Michael J; Nazarian, Ara; von Keudell, Arvind G
Highlights: We are reporting on predictive factors of necrotic muscle in patients undergoing leg fasciotomy. Crush injury and soft tissue injuries were at an increased odds of necrotic muscle, but only marginally significant. Patients with open fracture have a three-fold increase in odds of necrotic muscle at the time of fasciotomy. Abstract: Background: Acute physiologic compartment syndrome (ACS) is a disorder of increased intra-compartmental pressure leading to decreased tissue perfusion and muscle necrosis. Tissue ischemia can result in irreversible muscle and nerve injury and requires urgent fasciotomy. The aim of this study was to determine the factors associated with the presence of necrotic muscle in patients undergoing leg fasciotomy. Methods: This is a retrospective cohort study of all patients undergoing fasciotomies for ACS of the leg at two level 1 trauma centers from 2000 to 2015. We found 1, 028 patients who underwent leg fasciotomies. We excluded ACS at other sites than the leg, the index fasciotomy performed at an outside institution, prophylactic fasciotomy with no clinical signs of ACS, and patients with inadequate medical records. A total of 357 patients were included in the final analysis. We used bivariate analysis to assess which explanatory variables are associated with the main outcome measure, the presence of necrotic muscle at fasciotomy. We used multivariable regression analysis to determine association accounting for any confounding. Results: Of 357 cases of ACS of the leg, 14.6% of patients presented with an open fracture and 21.3% of patients were multiply injured. Overall, 14.3% of cases had muscle necrosis at the time of fasciotomy. Fifty-nine percent of patients with necrotic muscle required more than 3 debridements. Open fracture was the only statistically significant predictor of muscle necrosis (OR=2.8). Crush injury (OR=3.1) and soft tissue injuries (OR=2.8) were at an increased odds of necrotic muscle, but only marginally significant. Conclusion: ACS is a potentially limb threatening condition often associated with poor outcomes, particularly when the diagnosis is delayed. Patients with open fracture have a three-fold increase in odds of necrotic muscle at the time of fasciotomy.